NILAI-NILAI KARAKTER DAN ETNOMATEMATIKA DALAM PERMAINAN TRADISIONAL INGKLING - Safarinda Tri Handayani; Suparni Suparni (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
Ethnomathematics based learning is a solution for children to instill character values as well as foster a sense of love for local culture in the midst of technological advances. This study aim to conduct a literature review related to ethnomathematics, namely the relationship between mathematics and culture, especially in Javanese culture, one ofwhich is traditional games. The method used in this research is SLR (Systematic Literature Review). The data collection technique was carried out by documenting and reviewing five articles related to character values and ethnomathematics in the Ingkling traditional game published in the period 2017 to 2021 from the Googe Scholar database. The data analysis technique used is to identify, evaluate, and intepret all available in research. Based on the results of the study, it was found that there are ethnomathematics in the traditional game of Ingkling which has many roles, one of which can be used by junior high school students to understand the concept of opportunity. In addition, these traditional games also contain cultural values and character values in them.